Β‐Selective Aroylation of Activated Alkenes by Photoredox Catalysis. Issue 22 (17th April 2019) - Lei, Zhen; Banerjee, Arghya; Kusevska, Elena; Rizzo, Eric; Liu, Peng; Ngai, Ming‐Yu
Abstract: Late‐stage synthesis of α, β‐unsaturated aryl ketones remains an unmet challenge in organic synthesis. Reported herein is a photocatalytic non‐chain‐radical aroyl chlorination of alkenes by a 1, 3‐chlorine atom shift to form β‐chloroketones as masked enones that liberate the desired enones upon workup. This strategy suppresses side reactions of the enone products. The reaction tolerates a wide array of functional groups and complex molecules including derivatives of peptides, sugars, natural products, nucleosides, and marketed drugs. Notably, addition of 2, 6‐di‐ tert ‐butyl‐4‐methyl‐pyridine enhances the quantum yield and efficiency of the cross‐coupling reaction. Experimental and computational studies suggest a mechanism involving PCET, formation and reaction of an α‐chloro‐α‐hydroxy benzyl radical, and 1, 3‐chlorine atom shift. Abstract : Compatible : A photocatalytic β‐selective alkene aroylation, using readily available aroyl chlorides and activated alkenes, was developed. The synthetic utility of the reaction is highlighted by its broad functional‐group compatibility and high levels of chemo‐ and regioselectivity. The reaction is amenable to late‐stage functionalization of complex molecules including derivatives of sugars, peptides, natural products, nucleosides, and commercially available drugs.